AI Writing Assistants and Student Competence: A Linguistic Aspect - Прима, Вікторія Валентинівна; Прима, В. В.; Pryma, Viktoriia V.; Пеліван, Оксана Костянтинівна; Пеліван, О. К.; Pelivan, Oksana K.; Телецька, Тетяна Володимирівна; Телецька, Т. В.; Teletska, Tetiana V.; Цобенко, Ольга Василівна; Цобенко, О. В.; Tsobenko, Olha V.; et al. (Kuala Lumpur : AWEJ, 2025)
The study aims is to determine how AI tools affect the linguistic features of student writing. The research questions are: (1) How do AI writing tools affect the linguistic features of student writing? (2) What are university instructors’ attitudes toward the use of AI in writing instruction? The significance of this study arises from its addition to the literature on how AI technologies affect writing pedagogy and student learning in higher education. Using a mixed-methods design, the study questioned 60 university students enrolled in English for Academic Purposes (EAP) courses. Students were divided into two groups: students who used AI writing tools regularly and students who wrote without AI. Data were collected through essay writing tasks, student questionnaires, semi-structured interviews, and instructor feedback. Every subject wrote two essays, which were assessed for grammaticality, lexical diversity (measured in terms of the type-token ratio and vocabulary density), and coherence (based on rubric-based discourse analysis). Instructor feedback provided qualitative scores of writing depth and originality. Outcomes indicate that writing with AI significantly reduces grammatical errors, enhances vocabulary range, and promotes text cohesion by using programmed hints at linkages. However, there are serious concerns about the passive acceptance of AI suggestions by students that can compromise cognitive effort and critical thinking. There were instances when AI-produced work led to robotic sentence structure and formulaic arrangement. Teachers stressed the need for a pedagogical balance with AI tools without compromising students’ ability to write independently. The report concludes that, while AI can be a good writing tool, it should never be a substitute for but only a supplement to traditional writing pedagogy.
Pryma V. AI Writing Assistants and Student Competence: A Linguistic Aspect / V. Pryma, O. Pelivan, T. Teletska et al. // Arab World English Journal. – Kuala Lumpur : AWEJ, 2025. - Special Issue on Artificial Intelligence. - Р. 319–329. URL: https://dx.doi.org/10.24093/awej/AI.18
Keywords: academic writing; AI writing tools; coherence; grammatical accuracy; independent writing skills; linguistic development; pedagogical strategies; vocabulary diversity